Voice over internet protocol on mobile devices - Mao, G; Talevski, Alex; Chang, Elizabeth (IEEE, 2007)
Voice over Internet Protocol (VolP) is a way to carry out a telephone conversation over a data network. VoIP products promise converged telecommunications and data services that are cheaper, more versatile and provide good voice quality as compared to traditional offerings. Although VoIP is widely used, VoIP on mobile devices is still in its infancy. Currently, there are a number of VoIP solutions for mobile phones. However, VolP solutions developed using Java 2 Platform Micro Edition (J2ME) are not available. Java based solutions are widely compatible with many devices. In this paper; strong focus has been granted to cross-device compatibility through the use of the widely supported J2ME framework. The implemtation details of VolP client using J2ME are illustrated.